Harmonizing IPRs on Software Piracy: Empirics of Trajectories in Africa - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
In the current efforts of harmonizing the standards and enforcement of IPRs protection worldwide, this paper explores software piracy trajectories and dynamics in Africa. Using a battery of estimation techniques that ignore as well as integrate short-run disturbances in time-dynamic fashion, we answer the big questions policy makers are most likely to ask before harmonizing IPRs regimes in the battle against software piracy. Three main findings are established. (1) African countries with low software piracy rates are catching-up their counterparts with higher rates; implying despite existing divergent IPRs systems, convergence in piracy rate could be a genuine standard-setting platform. (2) Legal origins do not play a very significant role in the convergence process. (3) A genuine timeframe for standardizing IPRs laws in the fight against piracy is most likely between a horizon of 4 to 8 years. In other words, full (100%) convergence within the specified horizon will mean the enforcements of IPRs regimes without distinction of nationality and locality. Policy implications and caveats are discussed.
Keywords: F42; K42; O34; O38; O57; 330; Software piracy; Intellectual property rights; Panel data; Convergence